A survey of northern Victorian dairy farmers to investigate dairy calf management: colostrum feeding and management. Issue 4 (25th March 2018) - Phipps, AJ; Beggs, DS; Murray, AJ; Mansell, PD; Pyman, MF
Abstract : Objectives: To describe colostrum management practices carried out in northern Victorian dairy herds and to identify weaknesses in these areas that may affect calf health and welfare by comparing the results with the current industry recommendations Methods: A questionnaire to obtain information about colostrum management and calf‐rearing practices was sent to commercial dairy farming clients of Rochester Veterinary Practice between June and September 2013. The questionnaire consisted of a general herd overview and colostrum harvesting practices. Results: The response rate was 39% (58/150). Many dairy producers were not meeting the current industry recommendations in the following areas: (1) time of removal calf from the dam, (2) relying on calf suckling colostrum from the dam to achieve adequate passive transfer, (3) failing to supplement calves with colostrum, (4) feeding inadequate volumes of colostrum, (5) delayed colostrum harvesting, (6) pooling of colostrum, (7) failing to objectively assess colostrum quality or relying on visual assessment and (8) storing colostrum for a prolonged periods of time at ambient temperatures. Conclusion: The results from this survey highlight the need for greater awareness of industry standards for colostrum management and feeding hygiene.